The Beethoven Sonatas and the Creative Experience - Drake, Kenneth, 1930- (Book collections on Project MUSE., 1994)
Kenneth Drake regards the Beethoven sonatas as products of an inner necessity that pianists share with the composer. He encourages musicians to exercise intuition and independence of thought in studying the "32" and to seek not just performance skills but logical conclusions about ideas and relationships within the score.